Assessment of the potential danger of human consumption of food products from agricultural crops that were treated with the insecticide Oberon Rapid 240 SC, KS - Tkachenko , Inna; Antonenko, Anna; Borysenko, Andriy; Pelo , Ihor (The Ukrainian Scientific Medical Youth Journal, 2024)
сontaminated food products constitute one of the primary routes for the entry of residual pesticide levels into the human body, necessitating the establishment of appropriate regulations and rules for their safe use. The new insecticide Oberon Rapid 240 SC, CS was studied using both field and laboratory research methods, applied to the crops such as sunflower and maize. An analysis of the physico-chemical properties of the active ingredients of the preparation – spiromesifen and abamectin – was conducted. The content of active ingredients in the growing plants was determined, and the permissible levels were justified in sunflower seeds and maize grains (spiromesifen – 0.002 mg/kg, abamectin – 0.01 mg/kg), in sunflower and maize oils (spiromesifen – 0.05 mg/kg, abamectin – 0.01 mg/kg). The obtained results allowed for the justification of harvest collection within 30 days, and based on the calculated integral hazard indicators, spiromesifen and abamectin were classified as Class 4/3 (slightly/moderately hazardous pesticides) for the consumption of food products, respectively.